EKSPERIMENTASI MODEL TEAM ASSISTED INDIVIDUALIZATION (TAI)DAN STUDENT TEAM ACHIEVEMENT DIVISION (STAD) PADA MATERI LOGARITMADITINJAU DARIMOTIVASI BELAJAR SISWA KELAS X SMA NEGERI SE-KABUPATEN PURWOREJO TAHUN PELAJARAN 2011/ 2012 - Darmono, Prasetiyo Budi; Riyadi, Riyadi; Budiyono, Budiyono (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The objective of this research was to investigate the effect of the learning models on achievement viewed from learning motivation (LM) of the students. The learning models compared were TAI, STAD and direct instruction (DI). The type of the research was quasi-experimental research with 3x3 factorial design. The population of this research was the students in grade X senior high school in Purworejo on academic year of 2011/2012. The size of the sample was 294 students, which was taken by using stratified cluster random sampling technique. The instruments used for data collection were achievement test and motivation questionnaire. The hypothesis test used unbalanced two ways analysis of variance. The results of the research were as follows. (1) STAD and TAI had the same achievement. STAD gave better achievement than DI. TAI and DI had the same achievment(2) The students with high and medium LM had same achievement. The students with high LM had better achievement than the students with low LM. The students with medium and low LM had same achievement (3) In STAD, The students with high and medium LM had same achievement. The students with high LM had better achievement than the students with low LM. The students with medium and low LM had same achievement. In TAI, The students with high and medium LM had same achievement. The students with high LM had better achievement than the students with low LM. The students with medium and low LM had same achievement In DI, The students with high and medium LM had same achievement. The students with high LM had better achievement than the students with low LM. The students with medium and low LM had same achievement. (4) At the students with high LM, STAD and TAI had the same achievement. STAD gave better achievement than DI. TAI and DI had the same achievment. At the students with medium LM, STAD and TAI had the same achievement. STAD gave better achievement than DI. TAI and DI had the same achievment The students with low LM, STAD and TAI had the same achievement. STAD gave better achievement than DI. TAI and DI had the same achievmentKey words: Teams Assisted Individualization, Student Team Achievement Division, Direct Instruction, Learning Motivation , Achievement.